ANALISIS PENILAIAN PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS RENDAH SEKOLAH DASAR - Siti Habibah; Irma Sintiya Safitri; Kaysa Ananda; Khoirunnisa; Silvina Noviyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the implementation of assessment in Indonesian language learning for lower grade elementary students. The research is motivated by the importance of assessment as a tool to measure and improve students' language skills, while in practice it is still not fully optimal. This study uses a qualitative descriptive approach conducted at SDN 198/1 Pasar Baru with a third-grade teacher as the main informant. Data were collected through observation, interviews, and documentation. The results show that the teacher has implemented assessment continuously through process and outcome assessment using written tests and oral questioning. Assessment has also considered students' learning processes and individual development. However, several problems were found, including differences in students' ability levels, limited variation in assessment methods, and unclear instructions during assessment activities. These constraints affect the accuracy and comprehensiveness of assessment results. Therefore, improvements are needed through the use of varied assessment techniques, adaptation of tasks to students’ characteristics, and clearer instructional delivery. Thus, assessment in Indonesian language learning is expected to be more effective, fair, and able to comprehensively reflect students’ language development.